Urachal Cyst, a Rare Cyst with Multiple Complications. (2008) - Hawary, Amr; Duffy, Peter
Abstract : Urachal cysts are rare, can be one of the forgotten causes of abdominal pain, and can present as adenocarcinoma of the bladder, along with many other presentations. There is a real need for physicians, general surgeons, and urologists to be acquainted with the different presentations and management of this rare condition.